Durable Response to the Combination of Atezolizumab With Platinum-Based Chemotherapy in an Untreated Non-Smoking Lung Adenocarcinoma Patient With BRAF V600E Mutation: A Case Report - Niu, Xiaomin; Sun, Yingjia; Planchard, David; Chiu, Luting; Bai, Jian; Ai, Xinghao; Lu, Shun (Frontiers in Oncology, 2021)
Background: Immune checkpoint inhibitor (ICPi) has become a major treatment in advanced non-small cell lung cancer (NSCLC) and demonstrated a clinical benefit for NSCLC patients with high programmed death ligand-1 (PD-L1) expression without EGFR/ALK/ROS1 drivers, however, the benefit in BRAF V600E NSCLC is so far unknown. Here, we report a case of prolonged tumor response to the combination of immunotherapy with chemotherapy in a non-smoking BRAF V600E NSCLC patient. Materials and Methods: We verify a co-expression of BRAF V600E mutation and PD-L1 high expression more than 50% on formalin-fixed paraffin-embedded tumor sample of a newly diagnosed lung adenocarcinoma patient by immunohistochemistry and BRAF V600E/EGFR/ALK/ROS1 Mutations Detection Kit. The tissue and liquid biopsies were further subjected to next-generation sequencing (NGS) for identification of mutations when progression on immunotherapy and BRAF inhibitor (BRAFi). The patient had provided written informed consent and authorized the publication of clinical case. Results: We demonstrate the case of 62-year-old female non-smoker with high PD-L1 expression and BRAF V600E mutated NSCLC. The progression-free survival (PFS) of first-line combination of atezolizumab with platinum-based chemotherapy and sequential treatment with BRAFi Vemurafenib are 20 months and 5.5 months, respectively. Conclusion: This case shows a durable response to ICPi in BARF V600E non-smoking lung adenocarcinoma with PFS of 20 months under atezolizumab plus chemotherapy treatment which is longer than BRAFi treatment. The case supports the idea that the combination immunotherapy may be an attractive option for BRAF V600E mutated non-smoking NSCLC with high PD-L1 expression.